Intolerance : love's struggle throughout the ages - Griffith, D. W. (David Wark), 1875-1948; Gish, Lillian, 1893-1993; Marsh, Mae, 1895-1968; Wark Producing Corporation; Cinetel Films ([Los Angeles, CA] : Wark Producing Corp., 1916)
Four separate, interwoven stories, unified by the common theme of man's inhumanity to man. The Babylonian story deals with the fall of Babylon in 538 B.C. The Judean story treats the life of Christ. The French story centers on the Massacre of St. Bartholomew's Day in 1572. The modern story is set in an American mill town and the slum area of an American city.
Originally released as a motion picture in 1916.
Lillian Gish, Mae Marsh, Fred Turner, Robert Harron, Sam De Grasse, Miriam Cooper, Howard Gaye, Bessie Love, George Walsh, Margery Wilson, Eugene Pallette, Spottiswoode Aitkin, Ruth Handforth, Constance Talmadge, Alfred Paget, Seena Owen.
Cinematographer, G.W. Bitzer; editors, James Smith, Rose Smith, G.W. Griffith; music, Joseph Carl Breil.
Summary from The films of D.W. Griffith by E. Wagenknecht and A. Slide.
Technical credits from the IMDb database.
Silent, with English intertitles and musical accompaniment.
Keywords: Poverty -- Drama; Social problems -- Drama; Jesus Christ -- Miracles -- Drama; Jesus Christ -- Crucifixion -- Drama; Jesus Christ -- Teachings -- Drama; Saint Bartholomew's Day, Massacre of, France, 1572 -- Drama; Babylon (Extinct city) -- Drama; Silent films; Social problem films; Feature films; Internet videos; Streaming video